2013
DOI: 10.4161/onci.22590
|View full text |Cite
|
Sign up to set email alerts
|

Human MHC Class I-restricted high avidity CD4+T cells generated by co-transfer of TCR and CD8 mediate efficient tumor rejection in vivo

Abstract: In this study, we generated human MHC Class I-restricted CD4+ T cells specific for Epstein-Barr virus (EBV) and cytomegalovirus (CMV), two herpesviridae associated with lymphoma, nasopharyngeal carcinoma and medulloblastoma, respectively. Retroviral transfer of virus-specific, HLA-A2-restricted TCR-coding genes generated CD4+ T cells that recognized HLA-A2/peptide multimers and produced cytokines when stimulated with MHC Class II-deficient cells presenting the relevant viral peptides in the context of HLA-A2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 38 publications
3
49
0
Order By: Relevance
“…We analyzed cytotoxicity of an optimized Chim scTCR pp65 Vα-Li(Vβ) + Cα compared with an unmodified scTCR pp65 generated from a human dcTCR [27] in a retroviral vector system in human T-cells (Suppl. Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed cytotoxicity of an optimized Chim scTCR pp65 Vα-Li(Vβ) + Cα compared with an unmodified scTCR pp65 generated from a human dcTCR [27] in a retroviral vector system in human T-cells (Suppl. Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…19 In a similar context, previous studies have investigated the feasibility of using HLA class I-restricted genemodified CD4 + T cells after transfer of the TCR gene from a targetspecific CD8 + T-cell clone, [14][15][16]29,30 or from spontaneously Figure 4. Concurrent WT1-siTCR/CD4 + T cells stimulated with the cognate WT1 epitope, but not NGM-CD4 + T cells, enhance WT1-responsive proliferation and subsequent differentiation toward a memory T-cell phenotype mediated by WT1-siTCR/CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…12 To achieve effective tumor-specific helper T-cell function, 13 employment of CD4 + T cells that have been gene modified to target wellcharacterized HLA class I-restricted tumor antigens would seem to be a more attractive option than ex vivo expansion of CD4 + T cells by stimulation with HLA class II-restricted epitopes, as the latter is too time-consuming and labor-intensive. However, the use of gene-modified CD4 + T cells still remains at the preclinical stage, 11,[14][15][16] and to our knowledge, no study has yet investigated this approach for treatment of human leukemia. In the present study, therefore, targeting Wilms' tumor 1 (WT1), a well-studied leukemia-associated antigen, 17 we examined this concept with a view to its possible clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…Three of the trials are testing TCR constructs (WT1 and CMV specific) developed by the Stauss and Morris research group [34][35][36] and manufactured at the Great Ormond Street clinical production facility. The UK Cell Therapy Catapult has invested in the WT1-TCR gene therapy phase I clinical trial program and this partnership will oversee its subsequent commercialization, pending results of the early phase trials.…”
Section: Royal Free London Hospital University College London Hospitmentioning
confidence: 99%
“…The group is also leading translational application of emerging nuclease reagents including TALENs for the generation of universal Tcells depleted of alloreactive T-cell receptors. Within University College London, Prof. Hans Stauss and Dr. Emma Morris have shown that TCR-redirected T-cells can function in vitro and in vivo targeting tumor or viral antigens supporting clinical trial activity 34,41,42 and also that modifications to TCR sequences or transfer of additional molecules can enhance TCR expression and in vivo T-cell function, 43,44 that clinical-grade gene-modified cell products can be generated, 45,46 and that tolerance to tumor-associated antigens may be overcome. 47 Moreover, the group has also shown that genetic engineering of HSCs can alter the specificity of developing T-cells 48 and, in collaboration with others, has shown that gene-modified antigen-specific Tregs have suppressive function in vivo.…”
Section: Preclinical Activitymentioning
confidence: 99%